Behavioral and Emotional Problems Associated With Convergence Insufficiency in Children: An Open Trial. (October 2016) - Borsting, Eric; Mitchell, G. Lynn; Arnold, L. Eugene; Scheiman, Mitchell; Chase, Christopher; Kulp, Marjean; Cotter, Susan; ,
Objective: This study investigated behavioral and emotional characteristics of children with convergence insufficiency (CI), before and after treatment with office-based vergence accommodative therapy (OBVAT).Method: Parents of 44 children ages 9 to 17 years with symptomatic CI completed the Conners 3 ADHD Index and the Child Behavior Checklist (CBCL) before and after OBVAT. Pre-treatment scores were compared with normative data and post-treatment scores were compared with baseline using the Wilcoxon sign rank test.Results: Following OBVAT, CI children showed a significant mean improvement ( p < .0001, effect size of 0.58) on the Conners 3 ADHD Index with the largest changes occurring in the 23 children who scored the highest at baseline. On the CBCL, anxious/depressed, somatic, and internalizing problems improved significantly ( p < .001, effect sizes of −0.36, −1.15, and −0.67, respectively).Conclusion: In an open trial, attention and internalizing problems improved significantly following treatment for CI.